Amelioration of TMAO through probiotics and its potential role in atherosclerosis - Din, Ahmad Ud; Hassan, Adil; Zhu, Yuan; Yin, Tieying; Gregersen, Hans; Wang, Guixue (Applied microbiology and biotechnology, 2019)
Atherosclerosis is a major cause of mortalities and morbidities worldwide. It is associated with hyperlipidemia and inflammation, and become chronic by triggering metabolites in different metabolic pathways. Disturbance in the human gut microbiota is now considered a critical factor in the atherosclerosis. Trimethylamine-N-oxide (TMAO) attracts attention and is regarded as a vital contributor in the development of atherosclerosis. TMAO is generated from its dietary precursors choline, carnitine, and phosphatidylcholine by gut microbiota into an intermediate compound known as trimethylamine (TMA), which is then oxidized into TMAO by hepatic flavin monooxygenases. The present review focus on advances in TMAO preventing strategies through probiotics, including, modulation of gut microbiome, metabolomics profile, miRNA, or probiotic antagonistic abilities. Furthermore, possible recommendations based on relevant literature have been presented, which could be applied in probiotics and atherosclerosis-preventing strategies.